Fulfilling the journalistic principles of truth and objectivity in the context of mediatisation of political communication – the terrorist attacks in Paris in November 2015 - Leśniczak, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The mediatisation of political communication indicates two main functions of the mass media: they report on events from the world of politics and create the images of political actors in the eyes of the public. I attempt to answer the question: can one talk about respecting the basic principles of journalistic ethics (the truth and the objectivity principles) in the times of the mediatisation of the public sphere? The theme of the article applies to terrorism, which is a form of political communication, having its own special expression. The activities of terrorist organisations influence the actions of the leaders of political life, citizens and the mass media. The research material consisted of Polish opinion-making weeklies Newsweek Polska and Polityka and national dailies in their printed versions: Gazeta Wyborcza and Rzeczpospolita. The time frame covered a period from 1 November 2015 to 11 December 2015. The topic of the article was treated as a case study.